Vapor phase oxidation of 4-fluorotoluene over vanadia-titania catalyst - Maurya, S. K.; Patil, P.; Shubhangi B. Umbarkar; Gurjar, M. K.; Dongare, Mohan K.; Rudiger, S.; Kemnitz, E. (Journal of Molecular Catalysis A - Chemical, 2005)
The vapor phase oxidation of 4-fluorotoluene has been carried out over vanadia-titania catalysts with moderate conversion and selectivity for 4-fluorobenzaldehyde. Two series of V2O5/TiO2 catalysts with 1-10 mol% vanadia were prepared by sol-gel technique using vanadium and titanium peroxide as vanadia and titania precursors respectively and by impregnation technique using vanadium peroxide on anatase titania support. The samples were characterized by X-ray diffraction, NH3-TPD, FT-IR and BET surface area measurements. The XRD of the catalysts prepared by impregnation technique showed retention of the anatase titania whereas the catalysts prepared by sol-gel technique showed the formation of rutile titania with minor amount of anatase phase at lower vanadia content (1-3 %), which completely transformed into anatase phase at higher vanadia loading. The samples prepared by sol-gel method showed higher acidity and surface area compared to the samples prepared by impregnation. Pyridine adsorption study by FT-IR revealed the presence of Lewis acidity at lower vanadia loading (1-3 %) and presence of both Lewis as well as Bronsted acidity at higher vanadia loading. The catalytic activity for oxidation of 4-fluorotoluene increased with vanadia loading in the sol-gel catalysts. The catalysts prepared by impregnation technique were found to be less active. However the selectivity for 4-fluorobenzaldehyde decreased with increase in vanadia content. The influence of vanadia loading, reaction temperature and contact time on the catalytic activity for 4-fluorotoluene oxidation has been investigated. The structure of the catalyst and its catalytic activity has been correlated. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Catalyst; fluorotoluene; Oxidation; vanadia-titania; vapor phase

Vanadia-titania thin films for photocatalytic degradation of formaldehyde in sunlight - Akbarzadeh, Rokhsareh; Shubhangi B. Umbarkar; Sonawane, Ravindra S.; Takle, Srikant; Dongare, Mohan K. (Applied Catalysis A-General, 2010)
Thin films of vanadia-titania with good adhesion to the substrates have been deposited on various substrates such as glass slides, glass helix and silica raschig rings by simple sol-gel dip coating process using vanadium and titanium peroxide gel. The optimum concentration of vanadia in titania for obtaining good uniform viscous gel was found to be 0.5-4 wt% beyond which the vanadia particles disturb the gel network, resulting in the formation of a gelatinous precipitate. The films of vanadia-titania as well as the dried powder of the bulk gel were characterized by different characterization techniques. Optical characterization by UV-vis spectrophotometer showed a shift in optical absorption wavelength to the visible region that may be due to the incorporation of vanadia into titania structure. The XRD revealed the formation of anatase phase in pure titania as well as titania with up to 2% vanadia loading, whereas formation of rutile as minor phase along with anatase as major phase was observed at higher vanadia loading. The XRD did not show any peaks of vanadia phase up to 5% vanadia loading indicating either incorporation of vanadia into titania structure or high dispersion of amorphous vanadia on titania support. The pure and vanadia doped TiO(2) thin films were evaluated for their photocatalytic activity for degradation of methylene blue as a model pollutant under sunlight. Doping Of V(2)O(5) in TiO(2) showed an increase in the photo-degradation rate of methylene blue by a factor of 3-6.6 times compared to pure TiO(2). The highest rate has been obtained for 4% V(2)O(5)-doped TiO(2) films. Vanadia doped TiO(2) thin films were also found to be very active for photocatalytic degradation of formaldehyde from aqueous solution in sunlight. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Formaldehyde; Methylene blue; Photocatalysis; Sunlight; Thin films; V(2)O(5)/TiO(2)

Vanadium-based highly active and selective catalysts for oxidative dehydrogenation of ethyl lactate to ethyl pyruvate - Doke, Dhananjay; Khomane, Sonali B.; Pandhare, Swati; Dongare, Mohan K.; Dumeignil, Franck; Umbarkar, Shubhangi (Applied Catalysis A: General, 2019)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Pyruvates are important intermediates for various bioactive and pharmaceutical molecules. Synthesis of pyruvates is challenging due to low selectivity, as the pyruvates are prone to polymerisation. In the present work, oxidative dehydrogenation of ethyl lactate to ethyl pyruvate was carried out under very mild conditions using vanadium-based homogeneous and heterogeneous catalysts in the presence of aqueous <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">t<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">-butyl hydroperoxide as an oxidant. Homogenous vanadium-based catalyst, VO(acac)<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in acetonitrile solvent, gave excellent conversion (upto 83%) with 100% selectivity to ethyl pyruvate at room temperature. However, the heterogeneous catalyst, V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> exhibited very high activity for oxidative dehydrogenation of ethyl lactate only at higher temperature (80 °C). At higher temperature, significant TBHP decomposition was observed if all TBHP was added in one lot. In case of ethyl lactate dehydrogenation using V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst at 80 °C with two equivalents TBHP, 60% ethyl lactate conversion with 100% TBHP conversions were observed after 5 h when all TBHP was added initially in the reaction mixture. However, the ethyl lactate conversion at 80 °C, after 5 h increased to 72% when the same amount of TBHP was added batch wise over a period of 4 h, indicating improved conversion of TBHP to ethyl pyruvate. The heterogeneous catalyst, V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> exhibited up to 98% conversion with 100% ethyl pyruvate selectivity at 80 °C after 10 h with 3 equivalent TBHP added batch wise. The homogeneous catalyst could not be reused while V<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> could be successfully recycled five times without catalytic performances loss. Oxidation proceeds by radical mechanism, as proved by experiment with radical scavenger.